Can Computer Virtual Influencers Replace Human Influencers in the Future? An Empirical Investigation in the Age of Digital Transformation - Al Masri, Yazeed; Hamadneh, Samer; Al-Dmour, Rand; Al-Okaily, Manaf (Jordan Journal of Business Administration, 2023)
Marketers often face challenges when pursuing and working with social-media influencers. However, these challenges can be bypassed when choosing virtual influencers. This paper investigates computer-generated virtual influencers’ impact on a new fashion brand associations and buying intentions. Drawing on virtual humans’ literature and human influencer marketing literature, this study utilizes a fictional fashion brand and manipulates this brand using a popular Instagram virtual influencer. To understand the effect of virtual influencers’ characteristics on brand associations and buying intentions, 225 survey forms were distributed using a random-sampling method. Structural equation modeling was used to examine the virtual influencer attributes’ effects on brand attitudes and buying intentions. The study concluded that replacing human influencers in the fashion context, especially for new brands to establish a proper brand positioning, is integral to success. The study contributes to influencers’ marketing literature by integrating the virtual influencer concept into a celebrity endorsement discourse. Furthermore, the study offers a blueprint for marketing managers who are keen to understand virtual influencers’ attributes required to have an effective endorsement.